Reflections on improving women's experiences of mentorship in Canadian coaching - Kramers, S.; Bean, C.; Hummell, C.; Allan, V.; Johnson, A.; Turnnidge, J. (International Sport Coaching Journal, 2024)
Despite recent advancements for women in leadership roles, women remain underrepresented in sport coaching contexts. Mentorship has been advocated as a potential avenue for advancing and sustaining the careers of women coaches. In line with this, national sporting bodies have implemented mentorship programs to pair new and aspiring women coaches with senior leaders. While recent evaluations show promising results, research is needed to understand how these programs are conceptualized, implemented, and experienced by program participants. The purpose of this study was to qualitatively explore stakeholders` experiences in two Canadian women in coaching mentorship programs. Perspectives were gathered from 21 Canadian sport stakeholders that included program mentees, mentors, and staff. Data were analyzed using a reflexive thematic approach. Findings demonstrate the need for purposefully recruiting both mentor and mentee coaches to sustain meaningful partnerships. Additionally, participants highlighted the need for sport organizations to situate women in coaching as a priority and engage in sponsorship and long-term planning for sustaining women`s advancements in coaching. This study explores women in coaching mentorship programs from multiple perspectives, which may inform future formalized mentorship opportunities for women coaches by addressing identified challenges and barriers.